2023
DOI: 10.2147/ppa.s390123
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Suite of Resources to Improve Patient Adherence to Compression Stockings: Application of Behavior Change Theory

Abstract: Purpose Poor patient adherence to compression stockings remains a difficult and pervasive problem for clinicians, with costly repercussions for patients and health-care systems. The purpose of this paper was to describe the application of behavior change theory to the systematic development of a suite of resources, aimed at improving patient adherence to wearing compression stockings. Methods Employing a non-empirical approach, behavior-change theory was used to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“… 30 It is likely that patient perception of threat and their coping strategies, including their perception of lymphoedema being a problem, their ability to don garments, garment cost, comfort, and employment contributes to their adherence to compression. 31 33 …”
Section: Discussionmentioning
confidence: 99%
“… 30 It is likely that patient perception of threat and their coping strategies, including their perception of lymphoedema being a problem, their ability to don garments, garment cost, comfort, and employment contributes to their adherence to compression. 31 33 …”
Section: Discussionmentioning
confidence: 99%
“…16 Ostby and Armer 17 and Bar et al 18 demonstrated poor adherence over a 20-year investigative period in relation to lower extremity lymphedema/venous disorders. 17,18 Adherence issues arise when patients need to wear a snug or tight garment to help contain edema for lifelong management. A person's dexterity and mobility can further contribute to poor adherence.…”
Section: Static Compressionmentioning
confidence: 99%
“…However, the donning and doffing of these garments remain a challenge, which can lead to poor adherence 16 . Ostby and Armer 17 and Bar et al 18 demonstrated poor adherence over a 20-year investigative period in relation to lower extremity lymphedema/venous disorders 17,18 . Adherence issues arise when patients need to wear a snug or tight garment to help contain edema for lifelong management.…”
Section: Treatment Modalitiesmentioning
confidence: 99%